Meretas Pulau Raja Sebagai Destinasi Unggulan Di Kabupaten Gorontalo Utara (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2016)
This study aims to explore the potential of islands which can be developed as an attraction for Tourism in North Gorontalo District. Through a qualitative approached, secondary data are taken by instantional and primary data are taken by interviewed on 10 informans at King Island and Dunu Village, observation and study of document. The data are analyzed following by rationale, theory, and based on assumption of research. The findings showed that the king island can be a popular tourism attraction in North Gorontalo District. It based on analysis of 4A aspects (ie. attractions, aminities, accessibilities, associations) and posibility of market. Concluded that even some elements of the fourth aspects are weakness, overall it can be categorized still classified as good and many visiting guests